Description of a new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Brazil - Costa, Sabrina Santos; Mariano, Rodolfo (Zootaxa, 2013)
A new species of Miroculis is described based on material from State of São Paulo, Brazil.The imago of the new species can be separated from other species of the genus by the following combination of characters: upper part of stalked portion of compound eyes with 12 facets in the longest row; forewing translucent tinged with brown, with transverse and longitudinal veins brown; general color of abdomen brown translucent; size of penis from 0.8 to 1.0 the size of forceps segment I.